2004
DOI: 10.1016/j.bcp.2004.03.024
|View full text |Cite
|
Sign up to set email alerts
|

PPARα agonists clofibrate and gemfibrozil inhibit cell growth, down-regulate hCG and up-regulate progesterone secretions in immortalized human trophoblast cells

Abstract: We studied effects of PPARalpha agonists clofibric acid and gemfibrozil on cell growth and functions of immortalized human extravillous trophoblast cells. Levels of DNA and protein gradually increased during incubation for 4 days. Gemfibrozil (>0.25mM) and clofibric acid (2.5mM) suppressed the rate of increase in DNA and protein. Specific activities of fatty acyl-CoA oxidase and catalase were increased to about 1.2-2.0 times the control value by 0.05mM gemfibrozil and 1.0 and 2.5mM clofibric acid after incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
(83 reference statements)
2
18
0
Order By: Relevance
“…Chance et al 32) reported that catalase activity in HepG2 cells was increased to about 1.4 times higher than the control value by 1.0 mM clofibric acid. In our results, the activity in trophoblast cells was increased to about 1.34 times the control value by 1.0 mM clofibric acid, 3) indicating that the sensitivity of catalase in trophoblast cells to clofibric acid is the same as that of human hepatocytes.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Chance et al 32) reported that catalase activity in HepG2 cells was increased to about 1.4 times higher than the control value by 1.0 mM clofibric acid. In our results, the activity in trophoblast cells was increased to about 1.34 times the control value by 1.0 mM clofibric acid, 3) indicating that the sensitivity of catalase in trophoblast cells to clofibric acid is the same as that of human hepatocytes.…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, proliferation (DNA and protein contents) was decreased to about 40 and 45% after 3 d in culture in the presence of 0.2 mM WY-14643 (Fig. 1) and 2.5 mM clofibric acid, 3) respectively. These results suggest that trophoblast cells are somewhat more susceptible to WY-14643 and clofibric acid than choriocarcinoma cells.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations